A note on the essential pseudospectra and application. Issue 8 (2nd August 2016) - Ammar, Aymen; Boukettaya, Bilel; Jeribi, Aref
Abstract : In this research article, we work with the notion of essential pseudospectra of closed, densely defined linear operators in the Banach space. We start by giving the definition and we investigate the characterization, the stability and some properties of these essential pseudospectra.